Ecology and Physiology of the Pathogenic Cyanobacterium Roseofilum reptotaenium - Laurie L. Richardson; Dina Stanić; Amanda May; Abigael Brownell; Miroslav Gantar; Shawn R. Campagna (Life, 2014)
Roseofilum reptotaenium is a gliding, filamentous, phycoerythrin-rich cyanobacterium that has been found only in the horizontally migrating, pathogenic microbial mat, black band disease (BBD) on Caribbean corals. R. reptotaenium dominates the BBD mat in terms of biomass and motility, and the filaments form the mat fabric. This cyanobacterium produces the cyanotoxin microcystin, predominately MC-LR, and can tolerate high levels of sulfide produced by sulfate reducing bacteria (SRB) that are also associated with BBD. Laboratory cultures of R. reptotaenium infect coral fragments, suggesting that the cyanobacterium is the primary pathogen of BBD, but since this species cannot grow axenically and Koch’s Postulates cannot be fulfilled, it cannot be proposed as a primary pathogen. However, R. reptotaenium does play several major pathogenic roles in this polymicrobial disease. Here, we provide an overview of the ecology of this coral pathogen and present new information on R. reptotaenium ecophysiology, including roles in the infection process, chemotactic and other motility responses, and the effect of pH on growth and motility. Additionally, we show, using metabolomics, that exposure of the BBD microbial community to the cyanotoxin MC-LR affects community metabolite profiles, in particular those associated with nucleic acid biosynthesis.